PERCEIVED TASK CHARACTERISTICS AND ITS EFFECT ON EMPLOYEE ENGAGEMENT AT PRIVATE COLLEGES IN SARAWAK - Muhammad Madi Bin Abdullah; Lau Hui Lin, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
This study examines five perceived task characteristics variables (decision-making autonomy, task variety, task significance, task identity, feedback from job) and its effect on employee engagement at six private college employees in Sarawak. Despite extensive research on employee engagement, very little empirical research has examined this area of study specifically in the context of Sarawak private colleges. A survey questionnaire was employed to collect the data. A total of 284 responses were analysed using SPSS version 22.0. The results of this study revealed that only feedback from job, task identity and decision-making autonomy are significantly and positively associated with employee engagement. Task significance and task variety were not significantly related to employee engagement. Most importantly, decision-making autonomy was perceived as a dominant task characteristic for employee engagement; it was associated with significant improvements on private colleges’ employee engagement. This study contributes to a better understanding of the effect of perceived task characteristics on employee engagement among private colleges in Sarawak. The implications for practice and suggestions for future research are discussed.